2013
DOI: 10.1093/nar/gkt1258
|View full text |Cite
|
Sign up to set email alerts
|

FeON-FeOFF: the Helicobacter pylori Fur regulator commutates iron-responsive transcription by discriminative readout of opposed DNA grooves

Abstract: Most transcriptional regulators bind nucleotide motifs in the major groove, although some are able to recognize molecular determinants conferred by the minor groove of DNA. Here we report a transcriptional commutator switch that exploits the alternative readout of grooves to mediate opposite output regulation for the same input signal. This mechanism accounts for the ability of the Helicobacter pylori Fur regulator to repress the expression of both iron-inducible and iron-repressible genes. When iron is scarce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
52
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(64 citation statements)
references
References 68 publications
9
52
0
3
Order By: Relevance
“…2A,B). This result was unexpected because previous reports indicated that apo-Fur is mainly a dimer while holo-Fur is prevalently represented by tetramers or higher order oligomers12. Because the high surface charge of mica can readily disrupt the protein quaternary structure, we used glutaraldehyde crosslinking to fix the Fur oligomeric states.…”
Section: Resultsmentioning
confidence: 86%
“…2A,B). This result was unexpected because previous reports indicated that apo-Fur is mainly a dimer while holo-Fur is prevalently represented by tetramers or higher order oligomers12. Because the high surface charge of mica can readily disrupt the protein quaternary structure, we used glutaraldehyde crosslinking to fix the Fur oligomeric states.…”
Section: Resultsmentioning
confidence: 86%
“…The holo-HpNikR model structure in the cis conformation was docked onto OP ureA using the data-driven docking program HADDOCK 2.1 [42,43] and a previously described protocol [44] that involves a two-stage protein-DNA docking approach [45]. In the first docking round, a rigid body energy minimization was carried out, 1000 structures were calculated and the 200 best solutions based on the intermolecular energy were used for a semiflexible, simulated annealing step followed by an explicit water refinement.…”
Section: Protein-dna Dockingmentioning
confidence: 99%
“…Nucleotide sequence analyses (Tables 2 and 3) revealed the presence of a nonsynonymous fur mutation in all of the HSO strains, and previous studies have shown that Fur regulates the expression of frpB1, fecA1, and pdxA (39,43,(45)(46)(47)(48). Therefore, we hypothesized that the variations in Fur observed among the output strains (i.e., the WT [Fur-R88], Fur-R88H, or Fur-P45T) might account for the differences in frpB1, fecA1, and FIG 3 HSO strains demonstrate increased catalase enzymatic activity and elevated frpB1, pdxA, and fecA1 transcript levels.…”
Section: Figmentioning
confidence: 69%
“…Like Fur in other bacterial species, H. pylori Fur can, in the presence of ferrous iron, repress transcription by binding fur box sequences upstream of target genes. frpB1, fecA1, and pdxA are examples of H. pylori genes repressed by iron-bound Fur (39,43,(45)(46)(47)(48). The Fur R88H and P45T mutations are each located close to Fur amino acid residues important for iron coordination of Fur (E90 and H42, respectively) (55), and therefore, we speculate that these mutations might affect the ability of Fur to regulate its target genes.…”
Section: Figmentioning
confidence: 99%